Apartheid’s black soldiers: Un-national wars and militaries in Southern Africa - Kleynhans, Evert (Scientia Militaria - South African Journal of Military Studies, 2022)
In his recent book, Apartheid’s black soldiers: Un-national wars and militaries in Southern Africa, Lennart Bolliger examines the history of black soldiers from Namibia and Angola who served in the security forces of apartheid South Africa from 1975 until 1989. He focuses specifically on the three all-male units that consisted predominantly of black troops that were commanded by white officers – 32 Battalion of the South African Defence Force (SADF), 101 Battalion of the South West Africa Territorial Force (SWATF), and the infamous paramilitary police unit, Koevoet. During this period, these soldiers primarily fought against the People’s Liberation Army of Namibia (PLAN) – the military wing of the Namibian liberation movement, the South West Africa People’s Organisation (SWAPO) – in the anticolonial struggle in Namibia, as well as the post-independence civil war waged in Angola. The book builds on some earlier works by Bolliger, as well as another work co-authored with Will Gordon.